Cross‐neutralization of RBD mutant strains of SARS‐CoV‐2 by convalescent patient derived antibodies. Issue 11 (22nd August 2021) - Lou, Yan; Zhao, Wenxiang; Wei, Haitao; Chu, Min; Chao, Ruihua; Yao, Hangping; Su, Junwei; Li, Yanan; Li, Xiulan; Cao, Yu; Feng, Yanyan; Wang, Ping; et al.
Abstract: Background: The emergence of COVID‐19 pandemic resulted in an urgent need for the development of therapeutic interventions. Of which, neutralizing antibodies play a crucial role in the prevention and resolution of viral infection. Methods: We generated antibody libraries from 18 different COVID‐19 recovered patients and screened neutralizing antibodies to SARS‐CoV‐2 and its mutants. After 3 rounds of panning, 456 positive phage clones were obtained with high affinity to RBD (receptor binding domain). Clones were then reconstituted into whole human IgG for epitope binning assay and all 19 IgG were classified into 6 different epitope groups or Bins. Results: Although all antibodies were found to bind RBD, the antibodies in Bin2 had superior inhibitory ability of the interaction between spike protein and angiotensin converting enzyme 2 receptor (ACE2). Most importantly, the antibodies from Bin2 showed stronger binding affinity or ability to mutant RBDs (N501Y, W463R, R408I, N354D, V367F, and N354D/D364Y) derived from different SARS‐CoV‐2 strains as well, suggesting the great potential of these antibodies in preventing infection of SARS‐CoV‐2 and its mutations. Furthermore, such neutralizing antibodies strongly restricted the binding of RBD to hACE2 overexpressed 293T cells. Consistently, these antibodies effectively neutralized wildtype and more transmissible mutant pseudovirus entry into hACE2 overexpressed 293T cells. In Vero‐E6 cells, one of these antibodies can even block the entry of live SARS‐CoV‐2 into cells at 12.5 nM. Conclusions: These results indicate that the neutralizing human antibodies from the patient‐derived antibody libraries have the potential to fight SARS‐CoV‐2 and its mutants in this global pandemic. Abstract : The antibody libraries were generated from different COVID‐19 recovered patients for panning neutralizing antibodies to SARS‐CoV‐2 and its mutants. Then the positive clones were sequenced and reconstituted into whole human IgG for epitope binning assay. Finally, the antibodies were demonstrated to have great potential in blocking the infection of SARS‐CoV‐2 and its mutants.